SOLVING THE STUDENTS’ SPEAKING DIFFICULTIES THROUGH INTERVIEW AND JOKE AT MTS AL-MUSLIMUN NW TEGAL BATULAYAR - Agus Salim (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This Action Research has been conducted to see how interview and joke are effective in solving the students’ speaking difficulties at MTs AL-Muslimun NW Tegal. This research is aimed at conducting an enjoy strategy to teach speaking. This research have been conducted since March 2015, it is done in four procedures in giving the treatment; planning, action, observing and reflecting. Then, pre-test and post-test are also the applied in collecting the data.  Meanwhile, the students consists two classes A and B, each class there are 23 students. B class was chosen as the sample. They are chosen because of  a reason: the students do not have motivation to learn English. It is proved with the findings in pre-test, most of them in answering and expressing their ideas got a lot of mistaken and do not know what to do. After the treatment done, the significant change happen. It could be seen from the finding at post-test, most of them in understanding and answering the question they got better. It also proved with their pronunciation, vocabularies, fluent and accuracy getting better and better.  It means that the interview and joke is one of the method teaching and learning good to be applied. This analyzing is temporarily dealing with the findings; it will be completed at the final report.